Edaravone Modulates Neuronal GPX4/ACSL4/5-LOX to Promote Recovery After Spinal Cord Injury - Pang, Yilin; Liu, Xinjie; Wang, Xu; Shi, Xuelian; Ma, Lei; Zhang, Yan; Zhou, Tiangang; Zhao, Chenxi; Zhang, Xu; Fan, Baoyou; Hao, Jian; Li, Wenxiang; et al. (Frontiers in Cell and Developmental Biology, 2022)
The FDA-approved drug Edaravone has a neuroprotective effect in spinal cord injury (SCI) and many other central nervous system diseases. However, its molecular mechanism remains unclear. Since edaravone is a lipid peroxidation (LP) scavenger, we hypothesize that edaravone exerts its neuroprotection effect by inhibiting ferroptosis. Edaravone treatment after SCI upregulates Glutathione peroxidase 4 (GPX4) and System Xc-light chain (xCT), which were anti-ferroptosis proteins. Edaravone downregulates pro-ferroptosis proteins Acyl-CoA Synthetase Long-Chain Family Member 4 and 5-lipoxygenase(5-LOX). The most significant changes of edaravone treatment occurs in the acute phase, 2 days post injury. Edarvone modulates neuronal GPX4/ACSL4/5-LOX in the spinal segment below the lesion, which are critical for maintain locomotion. Moreover, edaravone also modulate the GPX4/ACSL4/5-LOX in motor neuron in the spinal cord. Therefore, the secondary injury below the lesion site are reversed by edaravone via ferroptosis inhibition. The cytokine array revealed that edaravone upregulated some anti-inflammatory cytokines such as IL-10, IL-13 and Adiponectin. Edaravone reduced microgliosis and astrogliosis, indicating reduced neuroinflammation. Edaravone has a long-term effect on neuronal survival, spinal cord tissue sparing and motor function recovery. In summary, we revealed a novel mechanism of edaravone in inhibiting neuronal ferroptosis in SCI. This mechanism may be generalizable to other neurological diseases.